2016
DOI: 10.1002/jeab.186
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent cognitive processes in rat serial pattern learning: II. Discrimination learning, rule learning, chunk length, and multiple-item memories

Abstract: The current experiment examined the factors that determine acquisition for elements of highly structured serial patterns. Three groups of rats were trained on three patterns with parallel rule-based hierarchical structure, but with 3-, 4-, or 5-element chunks, each with a final violation element. Once rats mastered their patterns, probe patterns were introduced to answer several questions. To assess the extent to which the learned response pattern depended on intrachamber location cues for anticipating differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
2
14
0
2
Order By: Relevance
“…With regard to the cognitive and neural systems affected in the transgenerational effect observed in the current study, our previous research has shown that serial pattern learning in the SMC task recruits different and separable cognitive systems for learning violation element learning, chunk-boundary element learning, and within-chunk element learning (Muller & Fountain, 2010; 2016), as noted in the Introduction. Specifically, learning to anticipate violation elements depends on multiple-item memory, that is, learning to use multiple pattern elements to cue the proper next response on the violation trial (Kundey & Fountain, 2010; Muller & Fountain, 2010; Muller & Fountain, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…With regard to the cognitive and neural systems affected in the transgenerational effect observed in the current study, our previous research has shown that serial pattern learning in the SMC task recruits different and separable cognitive systems for learning violation element learning, chunk-boundary element learning, and within-chunk element learning (Muller & Fountain, 2010; 2016), as noted in the Introduction. Specifically, learning to anticipate violation elements depends on multiple-item memory, that is, learning to use multiple pattern elements to cue the proper next response on the violation trial (Kundey & Fountain, 2010; Muller & Fountain, 2010; Muller & Fountain, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Specifically, learning to anticipate violation elements depends on multiple-item memory, that is, learning to use multiple pattern elements to cue the proper next response on the violation trial (Kundey & Fountain, 2010; Muller & Fountain, 2010; Muller & Fountain, 2016). Although the specific neural system or systems required for multiple-item learning have not been identified, rats' ability to learn to anticipate violation elements, and to a lesser extent chunk-boundary elements, depends on intact muscarinic cholinergic and NMDAr systems (Chenoweth & Fountain, 2015; 2016; Fountain & Rowan, 2000; Fountain, Rowan, & Wollan, 2013). More generally, hippocampus appears to play a key role in tracking sequences of stimuli (Agster, Fortin, & Eichenbaum, 2002; Fortin, Agster, & Eichenbaum, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations